THE IMPORTANCE OF AI IN EDUCATION (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Today, artificial intelligence is developing at an unprecedented pace and covers almost all areas, including education. This article discusses the advantages of using AI (Artificial Intelligence) in education, its positive impact on the quality of education, its ability to organize the educational process qualitatively and create many conveniences in the educational process.